2018
DOI: 10.24908/pocus.v3i1.13301
|View full text |Cite
|
Sign up to set email alerts
|

Research: Emergency medicine residents’ acquisition of point-of-care ultrasound knowledge and their satisfaction with the flipped classroom andragogy

Abstract: Background: One of the traditional approaches for knowledge transfer in medical education is through face-to-face (F2F) teaching. We aimed to evaluate the acquisition of knowledge about point-of-care ultrasound (POCUS) and learner’s satisfaction with the flipped classroom (FC) teaching approach. Methods: This was a prospective, mixed-method, crossover study and included 29 emergency medicine (EM) residents in current training program. Over a period of three months, each resident was exposed to F2F and FC teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(137 reference statements)
0
7
0
Order By: Relevance
“…Assessments in these studies focused on very short-term knowledge and/or skill retention. Several studies have demonstrated long-term knowledge or confidence retention after several weeks or months [ 22 , 25 , 51 , 52 ], however, few studies have investigated long-term skill retention [ 22 ]. The importance of investigating long-term skill retention is evident both from the results of our pilot and our review of the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Assessments in these studies focused on very short-term knowledge and/or skill retention. Several studies have demonstrated long-term knowledge or confidence retention after several weeks or months [ 22 , 25 , 51 , 52 ], however, few studies have investigated long-term skill retention [ 22 ]. The importance of investigating long-term skill retention is evident both from the results of our pilot and our review of the literature.…”
Section: Discussionmentioning
confidence: 99%
“…A flipped classroom in POCUS education has shown to be superior to conventional face-to-face teaching for both immediate and 2 month follow-up results. 30 Interestingly, our follow-up OSCE results, with 26 out of 32 students having scored 100%, might be indicative that the flipped classroom played an important role in the student’s knowledge retention.…”
Section: Discussionmentioning
confidence: 77%
“…Assessments in these studies focused on very short-term knowledge and/or skill retention. Several studies have demonstrated long-term knowledge or con dence retention after several weeks or months [20,23,50,51], however, few studies have investigated long-term skill retention [20]. The importance of investigating long-term skill retention is evident both from the results of our pilot and our review of the literature.…”
Section: Single Primary Outcome Selection For a De Nitive Studymentioning
confidence: 84%